Religious Laws and Religious Crimes in Developing and Developed Countries - Bansal, Arpana; Kaur, Ramkiran (International Journal of Psychosocial Rehabilitation, 2021)
A moral and ethical code of conduct that is advocated and followed by people from all walks of life religious faiths around the world is known as "religious law." Christianity, for example, adheres to the principles laid out in the Old Testament and is therefore considered to be a religion that follows religious law. A branch of Hinduism known as the Shariah follows the principles of Dharma, the Vedas and other ancient texts. Sikhism is based on a synthesis of Buddhist, Hindu, Jain, and other religious beliefs, and holds that there is only one true divine being Jainism adheres to the scriptures, which include a list of rules. The 5 Oaths Vows of Anuvratas include non-violence, truthfulness and nonpossession; 3 Gunavratas (Subsidiary Vows); and 4 Siksavratas, which are the Vows that instruct and guide one's actions..Since independence, India has seen numerous instances of what are commonly referred to as "hate crimes" or "communal violence. Violence Against Religious Minorities Has a Serious Impact on India's Muslims, Sikhs, And Christians. It's mostly for social, economic, and political gains that this type of violence is used. In many cases, these acts of violence are met with mobs and, in others, direct collaboration with state actors, ranging from inciting violence through hate speech to denying the need for a thorough investigation after the fact.